Multismoothness in Banach Spaces - Bor-Luh Lin; T. S. S. R. K. Rao (International Journal of Mathematics and Mathematical Sciences)
In this paper, motivated by the results published by R. Khalil and A. Saleh in 2005, we study the notion of k-smooth points and the notion of k-smoothness, which are dual to the notion of k-rotundity. Generalizing these notions and combining smoothness with the recently introduced notion of unitary, we study classes of Banach spaces for which the vector space, spanned by the state space corresponding to a unit vector, is a closed set.